2021
DOI: 10.1177/02676591211049316
|View full text |Cite
|
Sign up to set email alerts
|

Clinical monitoring of activated clotting time during cardiothoracic surgery: comparing the Hemochron® Response and Hemochron® Signature Elite

Abstract: Introduction: The Activated Clotting Time (ACT) is commonly used to manage anticoagulation during cardiac surgery. The aim of this study was to compare the older manually operated Hemochron® Response and the automated Hemochron® Signature Elite. Methods: In this observational study the clinically relevant differences of both devices were investigated simultaneously, using duplicate measurements, in 29 patients who underwent a Coronary Artery Bypass Grafting (CABG) or Aortic Valve Replacement (AVR) in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…They concluded that results of devices with different mecha-nisms should not be used interchangeably. [17][18][19] These study agree with our findings that devices having different mechanisms of measurement show difference in results. These results should not be used interchangeably and same device should be used before and after heparin administration and till the correction of ACT by protamine.…”
Section: Discussionsupporting
confidence: 89%
“…They concluded that results of devices with different mecha-nisms should not be used interchangeably. [17][18][19] These study agree with our findings that devices having different mechanisms of measurement show difference in results. These results should not be used interchangeably and same device should be used before and after heparin administration and till the correction of ACT by protamine.…”
Section: Discussionsupporting
confidence: 89%
“…The use of functional point-of-care tests also supports the rational disposition of blood products, and thromboelastometry, thromboelastography, alongside activated clotting time are among the most commonly utilized POCTs in the operating room environment. [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%